Socio-Cultural Potentials of the CEMAC Zone for Sub-Regional Integration and Development - Silikam, Julie Jasmine; Essounga, Angeline Raymonde Ngo (Technium Social Sciences Journal, 2021)
From its creation on March 16, 1994 in N'Djaména and the effective start of its activities in 1999, many hopes were placed in the Economic and Monetary Community of Central Africa (CEMAC), made up of six States: Cameroon, Chad, the Central African Republic, the Republic of Congo, Equatorial Guinea and Gabon. In this area of a total surface of around 3 million km2, are living about 37 million inhabitants. Since the 1910s, many strategies have been developed with the aim of consolidating the process of integration and, increasing the wealth creation capacities of these states members. However, the populations, primary beneficiaries of any integration process, still have difficulties in detecting the impact of this process on their standard of living and on their life in general. This because, the leaders of the CEMAC governments have not been able to boost development in the region with the political and economic strategies put in place. Culture being described as a factor that can contribute to integration, our article aims to analyze the socio-cultural elements in this area that can help to facilitate the integration process within the CEMAC. In order to better reflect the impact of the cultural factor in the integration process of CEMAC member states, the theories of transnationalism, functionalism and constructivism will form the backbone of this research work.